La desnutrición relacionada a la morbi - mortalidad en pacientes con enfermedad renal crónica en hemodiálisis, Hospital Regional de Loreto, 2022 - 2023 - Trujillo Garcia, Norcka Milagros (2022)
Objective: To determine if malnutrition is related to a higher rate of morbidity and mortality in patients with end-stage chronic kidney disease receiving replacement therapy with hemodialysis at the regional hospital of Loreto from 2022 to 2023. Methodology: It is an observational study, prospective cohort design, which will be carried out in the hemodialysis unit of the Regional Hospital of Loreto; The study will follow up for 2 years and will include the participation of hemodialysis patients, to whom measurement instruments will be applied; Subjective Global Assessment (SGA) will be used to determine nutritional status. The population will consist of all patients diagnosed with terminal chronic kidney disease (eGFR < 15 ml/min/1.73 m2) who receive replacement therapy with hemodialysis in the hemodialysis unit of the regional hospital of Loreto from 2022 to 2023, the sampling will be by convenience, for which 100 patients will be taken as a sample, who will be followed up for 2 years, the statistical analysis will be done through the use of student's t and Chi square for the calculation of the association of variables. To provide the relative risk of death in incident hemodialysis patients, the risk ratios (HR) and the 95% confidence interval (CI) will be calculated. Results: the primary result will be a higher mortality rate in 24 months and a higher morbidity rate, and the secondary results will be: degree of malnutrition by age and sex; morbi-mortality rate by age and sex. Conclusions: it is a prospective design cohort study in which it will show us how important the degree of malnutrition is in hemodialysis patients for the appearance of different morbidities and mortality in this type of patients.